Eschatological Foundations of Christian Education: How our Beliefs about Christ's Return Impact our Educational Ministry Efforts - Estep, James Riley (Christian education journal, 2015)
Recent theological work on foundations of Christian education has explored a wide range of important systematic theology topics (e.g., sanctification, ecclesiology, pneumatology, Trinity, the nature of Scripture). An area that has not received much attention is eschatology. How do understandings of Christ's promised return impact the focus of educational ministries in the church? What is important for us to learn in this time of waiting? This paper focuses on biblical images and themes associated with waiting for Christ's return and key issues that should have an impact on Christian educators' ministry efforts. It explores how eschatological views give direction and shape to the church's teaching ministries.